2022
DOI: 10.3389/fimmu.2022.1028788
|View full text |Cite
|
Sign up to set email alerts
|

Detailed phenotypic and functional characterization of CMV-associated adaptive NK cells in rhesus macaques

Abstract: Previous research on adaptive NK cells in rhesus macaques suffered from the lack of specific antibodies to differentiate between inhibitory CD94/NKG2A and stimulatory CD94/NKG2C heterodimeric receptors. Recently we reported an expansion of NKG2C receptor-encoding genes in rhesus macaques, but their expression and functional role on primary NK cells remained unknown due to this deficit. Thus, we established monoclonal antibodies 4A8 and 7B1 which show identical specificities and bind to both NKG2C-1 and NKG2C-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Similar memory-like NK cell function has been observed in rhesus macaques following rhCMV and SIV infection (84). Recent research demonstrated that animals infected with rhesus cytomegalovirus (rhCMV) have expanded populations of NKG2C1+ and/or NKG2C2+ NK cells (85). Furthermore, single-cell RNAseq performed on rhCMV+ NK cells showed that NKG2C2 is the most highly transcribed of the three NKG2C genes (85).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar memory-like NK cell function has been observed in rhesus macaques following rhCMV and SIV infection (84). Recent research demonstrated that animals infected with rhesus cytomegalovirus (rhCMV) have expanded populations of NKG2C1+ and/or NKG2C2+ NK cells (85). Furthermore, single-cell RNAseq performed on rhCMV+ NK cells showed that NKG2C2 is the most highly transcribed of the three NKG2C genes (85).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research demonstrated that animals infected with rhesus cytomegalovirus (rhCMV) have expanded populations of NKG2C1+ and/or NKG2C2+ NK cells (85). Furthermore, single-cell RNAseq performed on rhCMV+ NK cells showed that NKG2C2 is the most highly transcribed of the three NKG2C genes (85). Though we cannot say with certainty, our experience with polymorphic immune gene families in macaques has shown that observations in cynomolgus macaques often extend to rhesus macaques.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their phenotypical adapta?ons, longevity, and ability to elicit specific recall responses, this kind of virus-specific memory NK cell is now commonly referred to as adap?ve NK cell. Notably, similar cells were also iden?fied in CMVinfected macaques (35)(36)(37). Moreover, a different type of long-living NK cell is also present in mice, recognizing MCMV-infected cells via recogni?on of the m157 protein by the s?mulatory Ly49H receptor (38).…”
mentioning
confidence: 87%
“…77 Due to the lack of specific reagents for macacine NKG2C, it has so far remained challenging to specifically define RhCMV-induced memory NK cell clones, but ongoing studies combining barcoding with single-cell RNA sequencing (scRNA-seq) 80 and novel antibodies specifically designed for macaque antigens hold promise to resolve these issues. 81 In humans, we recently revisited the hypothesis of NK cell clonal expansion and persistence utilizing mitochondrial mutations as cellendogenous barcodes. 9 The mitochondrial genome exists in many copies (100-1000s) per cell and has a higher mutation rate than F I G U R E 1 The memory NK cell compartment is composed of diverse clonal identities.…”
Section: Clonal Nk Cell Responses To CMVmentioning
confidence: 99%
“…Experimental infection with RhCMV initially induced polyclonal expansion, with discernible clonal shifts occurring around 2 months after infection 77 . Due to the lack of specific reagents for macacine NKG2C, it has so far remained challenging to specifically define RhCMV‐induced memory NK cell clones, but ongoing studies combining barcoding with single‐cell RNA sequencing (scRNA‐seq) 80 and novel antibodies specifically designed for macaque antigens hold promise to resolve these issues 81 …”
Section: Clonal Selection and Expansion Shape The Immune Repertoirementioning
confidence: 99%